TClC effectively suppresses the growth and metastasis of NSCLC via polypharmacology - Jing Lu; Ying Zhang; Chunyan Yan; Jingwen Liu; Dan Qi; Yue Zhou; Qinwen Wang; Juechen Yang; Jing Jiang; Benhao Wu; Meiling Yang; Weiwei Zhang; et al. (Bioactive Materials)
Despite significant advances in targeted therapies and immunotherapies, non-small cell lung cancer (NSCLC) continues to present a global health challenge, with a modest five-year survival rate of 28 %, largely due to the emergence of treatment-resistant and metastatic tumors. In response, we synthesized a novel bioactive compound, ethyl 6-chlorocoumarin-3-carboxylyl L-theanine (TClC), which significantly inhibited NSCLC growth, epithelial mesenchymal transition (EMT), migration, and invasion in vitro and tumor growth and metastasis in vivo without inducing toxicity. TClC disrupts autocrine loops that promote tumor progression, particularly in stem-like CD133-positive NSCLC (CD133+ LC) cells, which are pivotal in tumor metastasis. Through targeted molecular assays, we identified direct binding targets of TClC, including Akt, NF-κB, β-catenin, EZH2, and PD-L1. This interaction not only suppresses the expression of oncogenic factors and cancer stem cell markers but also downregulates the expression of a multidrug resistance transporter, underscoring the compound's polypharmacological potential. These results position TClC as a promising candidate for NSCLC treatment, signaling a new era in the development of cancer therapies that directly target multiple critical cancer pathways.